2009
DOI: 10.1128/jvi.00409-09
|View full text |Cite
|
Sign up to set email alerts
|

Shared and Group-Specific Features of the Rotavirus RNA Polymerase Reveal Potential Determinants of Gene Reassortment Restriction

Abstract: Rotaviruses (RVs) are nonenveloped, 11-segmented, double-stranded RNA viruses that are major pathogens associated with acute gastroenteritis. Group A, B, and C RVs have been isolated from humans; however, intergroup gene reassortment does not occur for reasons that remain unclear. This restriction might reflect the failure of the viral RNA-dependent RNA polymerase (RdRp; VP1) to recognize and replicate the RNA of a different group. To address this possibility, we contrasted the sequences, structures, and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 44 publications
(74 reference statements)
3
64
1
Order By: Relevance
“…The RNA polymerase domain in VP1 and N-terminal RNA-binding domain in NSP3 are evidently conserved compared with other regions in individual proteins, as also found in cognate proteins of GAR (Rao et al, 1995;Heiman et al, 2008;McDonald et al, 2009). In these domains, some amino acids/motifs are commonly found among GAR, GBR and GCR, despite high sequence diversity among them.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The RNA polymerase domain in VP1 and N-terminal RNA-binding domain in NSP3 are evidently conserved compared with other regions in individual proteins, as also found in cognate proteins of GAR (Rao et al, 1995;Heiman et al, 2008;McDonald et al, 2009). In these domains, some amino acids/motifs are commonly found among GAR, GBR and GCR, despite high sequence diversity among them.…”
Section: Discussionmentioning
confidence: 93%
“…The RNA polymerase domain of VP1 (finger I, II, palm I, II, and thumb) located in the central portion (469 aa) (McDonald et al, 2009), including functionally critical motifs shared by different rotavirus groups as well as other RNA viruses (Cohen et al, 1989;Nagashima et al, 2008), was highly conserved among GBRs (Fig. 2).…”
Section: Divergent Regions In Viral Proteinsmentioning
confidence: 99%
“…Since the proposal that RV-A classification should be based on all 11 RV-A gene segments (Matthijnssens et al, 2008b), the number of studies reporting RV-A full genome sequences has increased Esona et al, 2010bMatthijnssens et al, 2008a;McDonald et al, 2009McDonald et al, , 2011MijatovicRustempasic et al, 2011). Previous studies have shown that the predominance of a specific G type is related to the emergence of atypical VP7 lineages Parra, 2009;Parra et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The genetic variability of RV-A strains is the result of accumulation of single nucleotide mutations (genetic drift) and sudden changes in the RV-A genome (genetic shift), primarily by reassortment and recombination events (Estes and Kapikian, 2007;Matthijnssens et al, 2008c;McDonald et al, 2009;Ramig, 1997). Since the proposal that RV-A classification should be based on all 11 RV-A gene segments (Matthijnssens et al, 2008b), the number of studies reporting RV-A full genome sequences has increased Esona et al, 2010bMatthijnssens et al, 2008a;McDonald et al, 2009McDonald et al, , 2011MijatovicRustempasic et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…If complementarity is involved in the packaging mechanisms of RVA, co-evolution of complementary nucleotides may suppress reassortments between distantly related strains (Heiman et al, 2008;McDonald et al, 2009aMcDonald et al, , 2009bMcDonald and Patton, 2011;. Reassortment is known to occur within mammalian and avian RVA (Ward et al, 1990;Schumann et al, 2009).…”
mentioning
confidence: 99%